Conceptually Confused, but on a Field Level? A Method for Conceptual Analysis and its Application - Jaana Tähtinen; Virpi Havila (Sage, 2022)
This paper develops and applies a Conceptual Analysis Method (CAM). The CAM is a critical reflection on multiple definitions and descriptions of concepts and terms all used to refer to a phenomenon or the experiences of it. The method particularly helps researchers working in emerging research fields to discover any conceptual confusion and elucidate multiple terms and concepts. We demonstrate the utility of the CAM by discovering conceptual confusion on an example field: business relationship uncoupling, and elucidating its terms and concepts. This paper adds to the discussion on the importance of conscious conceptual language for theory development, on the level of a research field.